Water Resources Management in Central Asia - Zonn, Igor S.; Zhiltsov, Sergey S.; Kostianoy, Andrey G.; Semenov, Aleksandr V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book reviews the current status of water resources management in Central Asian countries, and outlines the history, policies and cross-border cooperation regarding water resources management in the region. Particular attention is paid to the evolution of water resources management in Central Asia, past and future water transfer projects, specific problems concerning water use and pollution, and national approaches to water management in Kazakhstan, Kyrgyzstan and Tajikistan, as well as to related conflicts between the Central Asian countries. Together with the companion volumes on Water Resources in Central Asia: International Context and Water Bodies and Climate Change in Central Asia, it offers a valuable source of information for a broad readership, from students and scientists interested in the environmental sciences, to policymakers and practitioners working in the fields of water resources policy and management, international relations, and environmental issues.
Introduction -- Role of water resources in the modern world -- Evolution of Water Resources Management in Central Asia -- Water resources transfer in Central Asia: Projects, results and perspectives -- Legal aspects of water resources management in Central Asian countries -- Main Problems of Water Resources Use in Central Asia -- Water bodies and water resources of the Kyrgyz Republic and challenges in their transboundary use -- Tajikistan Water Resources and Water Management Issues -- Current Hydropower Potential of Kazakhstan -- The level of anthropogenic pollution of the Kapshagay Water Reservoir, Republic of Kazakhstan -- Current state of water resources and problems of their use in border regions of Russia (the Ob-Irtysh Basin as a case study) -- Conclusions.
Keywords: Environmental chemistry; Water; Pollution; Environmental Chemistry; Water, general; Pollution, general